The acquisition of immovable properties by foreigners in European Union and Turkey - Balkan, Ali Harun (My University, 2010)
Yabancıların taşınmaz edinmesine ilişkin mevzuat genellikle farklı öncelikler ve farklı hukuk sistemlerinin bakış açılarından bir çok sınırlama içerir. Özellikle AB hukukunun bu konudaki dava hukuku oldukça ilginç kararlar içerir. Bu tezde AB üyesi devleti vatandaşlarının diğer AB üyesi ülkelerde mal edinmeleri konusunda Avrupa Adalet mahkemesi kararları incelenecektir. Cevap aranılan soru, AB entegresyon sürecinde, sınırlamaların sınırı nerede olacaktır sorusudur. Bu sorunun cevabı, birliğe üye olan ülkelerin üye olma süreci, derogasyonları ve Avrupa Adalet Dİvanı kararları ışığı altında aranacaktır. Yine bu tezde mevcut haliyle Türk mevzuatında yabancıların gayrimenkul edinmesi ile hükümler de değerlendirilecektir. Son olarak, Adalet divanı kararları da dikkate alınarak, bir system önerisi oluşturulacaktır. Bu öneri spekülasyonun, optimal olmayan kullanımın ve arazilerin parçalanmasının engellenmesi üzerine kurgulanacaktır.

The legislations on acquisition of immovable properties by foreigners consist many limitations based on different priorities and approaches of the law systems. Especially, EJC’s case law consists many interesting judgments. In these thesis, we will examine acquisition of immovable properties by citizens of member states under the light of case-law of European Court of Justice. We will try to answer the question of the limit of limitations. Such an answer will be sought to found under the process of negotiations, derogations and case law. In addition to that, Turkish current legislation will be examined regarding to the immovable properties by foreigners will be taken in the consideration. Eventually, a system proposal will be developed under the light of the case law of European Court of Justice. This proposal will be established on prevention of speculation, non-use and under-use and fragmentation of land.
Keywords: Avrupa Birliği Hukuku; Avrupa Birliği_Türkiye